Language, cognition, and human nature - Pinker, Steven (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references and indexes; Formal models of language learning -- A computational theory of the mental imagery medium -- Rules and connections in human language / with Alan Prince -- When does human object recognition use a viewer-centered reference frame? / with Michael Tarr -- Natural language and natural selection / with Paul Bloom -- The acquisition of argument structure -- The nature of human concepts : evidence from an unusual source / with Alan Prince -- Why nature and nurture won't go away -- The faculty of language : what's special about it? / with Ray Jackendoff -- So how does the mind work? -- Deep commonalities between life and mind -- Rationales for indirect speech : the theory of the strategic speaker / with James Lee -- The cognitive niche : coevolution of intelligence, sociality, and language